Menstrual Taboo; Menguji Wasathiyatul Islam Pada Menstruasi - Syahrul Rahman; Hamdani Hamdani (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Al-Quran gives a firm statement about Muslims as ummatan wasathan which interpreted as the best people or middle people. Al-Quran scholar state that the term of wasathan in al-Baqarah verse 143 applies to all aspect of life, including the aspects of faith, law, worship and others. Based on this verse, moderate Islamic concept is presented, it's just this term is often used to assess religious understanding within the body of Islam itself, while the row of verses talks about the mystical conflicts of the companions of the Prophet after hearing the comments of the Jews and Christians regarding the movement Qibla direction of Muslims. There was a shift in the use of term wasathiyah in Indonesia from a comparison between people (religion) to a comparison of religious understanding in Islam its self. The approach method used in this article is an interpretive approach This article aims to examine the modernity of Islam in the legal aspects of menstruation compared to Judaism and Christianity. These three religious teachings see women who are menstruating should be kept away, it's just there are significant differences in its application. Some make a menstruation women kept away physically like Jews and Christianity. Some others avoid it in the sense they are not justified to perform ritual worship like Islam. This research proves that the teachings of Islam are lighter / more moderate in viewing women who are menstruating compared to Judaism and Christianity and at the same time this confirms the interpretation of scholars towards the word wasathiyah applies to all aspects of life including menstruation.